Modeling The Habitat Suitability of Dare Monkey (Macaca maura Hr Schinz 1825) in Bantimurung Bulusaraung National Park, South Sulawesi - pramana, gede tragya suartika; Prasetyo, Lilik Budi; Iskandar, Entang (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
Sulawesi Island is the center of the Wallacea area which has high biodiversity and is inhabited by several endemic species of plants and animals, one of which is the dare monkey (Macaca maura HR Schinz 1825). This study aims to analyze habitat suitability and the effect of environmental variables on the habitat suitability of dare monkeys in the Bantimurung Bulusaraung National Park area. This research was conducted through the development of a species distribution approach model using Maxent ver 3.4.4. The results showed that the AUC value of the dare monkey habitat suitability model was 0.893 with a standard deviation of ±0.015 which is a feasible predictive model with suitable habitat area is 138.43 km2 (20%) and not suitable 538.44 km2 (80%). The suitable habitat area is divided into 3 classes, namely the low suitability class 90.11 km2 (65%), the medium suitability class 25.58 km2 (18%) and the high suitability class 22.74 km2 (16%). while the environmental variables that play a role and affect the presence of dare monkeys are land cover (35.1%), distance from the road (32.2%), distance from agricultural areas (13.1%), distance from rivers (12.1%), slope (3.6%), altitude (2.6%) and temperature (1